2007
DOI: 10.1007/s00402-007-0386-8
|View full text |Cite
|
Sign up to set email alerts
|

Knee arthrodesis for limb salvage with an intramedullary coupled nail

Abstract: We have found that the Mayday nail offers a straightforward, reproducible surgical option for difficult salvage surgery. Good results have been obtained in the majority of cases, avoiding the devastating consequences of above knee amputation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…Although external fixation devices, for example, have the benefit of a shorter operation time, they are associated with various complications [24], such as recurring pin infection and pin loosening, malunion, and the necessity of a removal of the fixator afterwards [6,20,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although external fixation devices, for example, have the benefit of a shorter operation time, they are associated with various complications [24], such as recurring pin infection and pin loosening, malunion, and the necessity of a removal of the fixator afterwards [6,20,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although success rates of 80% to 100% have been reported after primary, biologic arthrodesis in patients without prior TKA [9,14,19,30,31,37,44], the success rate of arthrodesis performed in patients with an infection at the site of a TKA has been reported to be much lower [8]. However better results in terms of complication rates have been reported using metal implants than biologic reconstruction [2,8,9,11,13,23,33,42,45,47].Whereas Gosheger et al reported no infections in three arthrodeses with the MUTARS 1 implant [16] and Bartlett et al reported one infection in 10 Stanmore implants [3], there were nine infections in our 31 patients. This finding might be because the mean followup for our series was substantially longer at 9.5 years compared with the other series and of our infections were late infections.…”
mentioning
confidence: 99%
“…11 Furthermore, dual-plane and circular external fixators provide good stability in case of an infected operated joint.…”
Section: Resultsmentioning
confidence: 99%